Identification and Ranking of Organizational Factors Affecting the Formation of Deviant Behaviors in the Workplace of Al-Qadisiyah University, Republic of Iraq - Muhammad Sajet, Sadegh Sarhan; Hadi Peykani, Mehraban; Abbas Behiyeh, Zaki Muhammad; Shahtalebi, Badri (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The present study aimed to identify and rank the organizational factors influencing the formation of deviant behaviors in the workplace at Al-Qadisiyah University, Iraq. Methodology: This research employed a mixed-method approach (qualitative-quantitative). The participants in the qualitative section included 21 experts and administrative and educational managers from Al-Qadisiyah University, Iraq, who were interviewed using semi-structured interviews until theoretical saturation was reached. Data were analyzed using a three-stage coding process (initial, organizing, and overarching) for thematic analysis. In the quantitative section, the statistical population consisted of 180 managers and employees at Al-Qadisiyah University. Using the Krejcie and Morgan table and stratified random sampling, 120 individuals were selected as the sample. The validity of the questionnaire was confirmed through convergent and discriminant validity, and its reliability was confirmed using Cronbach’s alpha (0.862). Data were analyzed using factor analysis and covariance-based structural equation modeling with the AMOS graphical software. Findings: The findings from the qualitative section identified 101 indicators, 14 components, and 3 dimensions, which included managerial factors, job-related factors, and structural factors. The quantitative findings indicated a good fit for all dimensions and components. The ranking results for organizational factors influencing the formation of deviant behaviors in the workplace were as follows: managerial factors, job-related factors, and structural factors. Conclusion: It can be concluded that managerial factors play a significant role in the formation of deviant behaviors in the workplace, and therefore, stakeholders should pay attention to these factors.